Beyond the Politics of Domination: Aristocratic Culture in Nietzsche (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
Nietzsche’s “aristocratic radicalism” has been interpreted to mean either thatNietzsche favors returning to pre-modern political models of aristocratic society which are completely incompatible with modern democracy, or that aristocratism is a radical variant of liberal individualism, an aesthetic and apolitical attitude towards life. In this paper I argue that Nietzsche’s aristocratism fits neither of the above interpretations. Rather, Nietzsche understands aristocratic society in spiritual-cultural terms. In the light of ananalysis of nobility, an aristocratic society and culture must be a horizontal ordering of equally respected powers for and against each other that aims at the elevation of the significance of the singular individual’s responsibility.
Keywords: Nietzsche; culture; politics; order of rank (Rangordnung); responsibility; aristocratism